CERITA LISAN “YONG DOLLAH”: PEWARISAN DAN RESISTENSI BUDAYA ORANG MELAYU BENGKALIS - Marhalim Zain (Madah: Jurnal Bahasa dan Sastra, 2014)
Humorous stories Yong Dollah is one form of oral literature that very popular in  Bengkalis Malay community. Yong Dollah is a nickname of a Malay's character. His real name is Abdullah bin Endong, who is expected to be born in Bengkalis around 1906. One of the inheritance strategy of Yong Dollah oral stories which makes distribution spreaded widely and became popular by telling the story about him in front of  friends at the coffee shop, in  spare time. Activities "drink coffee in the spare time" is then often called kahwe. It is also that later differentiate oral stories inheritance system in general, which is usually passed down through families. In addition, this study also wants to show that, through kahwe tradition inheritance system is closely linked to the culture of the  Bengkalis Malay resistance through Yong Dollah oral stories  against colonialism and globalization. It also shows that the oral tradition is still believed to have the power to operate the functions of transformative in people's lives.  Cerita-cerita jenaka Yong Dollah adalah salah satu bentuk sastra lisan yang sangat populer di lingkungan masyarakat Melayu Bengkalis. Yong Dollah adalah sebuah nama panggilan dari seorang tokoh Melayu bernama asli Abdullah bin Endong, yang diperkirakan lahir di Bengkalis sekitar tahun 1906. Salah satu strategi pewarisan cerita-cerita lisan Yong Dollah yang membuat penyebarannya meluas dan menjadi populer adalah dengan menuturkannya di depan kawan-kawannya di kedai kopi, di waktu senggang. Aktivitas ―minum kopi di waktu senggang‖ ini kemudian kerap disebut kahwe. Hal ini juga yang kemudian membedakan sistem pewarisan cerita lisan pada umumnya, yang biasanya diwariskan melalui keluarga. Selain itu, penelitian ini juga hendak menunjukkan bahwa sistem pewarisan melalui tradisi kahwe ini terkait dengan upaya resistensi budaya orang Melayu Bengkalis melalui cerita-cerita lisan Yong Dollah terhadap kolonialisme dan globalisasi. Hal ini juga menunjukkan bahwa tradisi lisan masih dipercaya memiliki kekuatan dalam mengoperasikan fungsi-fungsi transformatifnya dalam kehidupan masyarakat.